IMPLEMENTASI LMS (LEARNING MANAGEMENT SYSTEM) MOODLE TERHADAP HASIL BELAJAR MAHASISWA DI UNIVERSITAS QUALITY - DEDI HOLDEN SIMBOLON (JURNAL CURERE, 2021)
This study aims to determine the effectiveness of using Moodle's LMS (Learning Management System) media on student learning outcomes and activity levels. The research sample was determined using purposive sampling technique, namely students who took the research methodology course. The data collection technique used a learning outcome test instrument. From the data analysis, it was obtained that the students' pretest average score was 55.76 and the standard deviation was 7.13 with the highest score of 75 and the lowest was 46. After the material was taught from the post-test results, it was obtained an average of 90.26 and a standard deviation of 1.75 with the highest score of 94 and the lowest of The average level of student activity was 68.98 and a standard deviation of 2.65 with the highest score of 95 and the lowest was 79. From the results of the study, it was concluded that the application of Moodle's LMS (Learning Management System) media in learning had a positive impact on student learning outcomes and activities.